Анализ современных методов оценки состояния окружающей среды при воздействии негативных факторов элементов ЯТЦ - Гнедая, И. Л.; Диордица, В. А.; Кожевникова, М. Ф.; Левенец, В. В. (НТУ "ХПИ", 2007)
Зроблено огляд сучасних підходів до процедури оцінки стану об’єктів навколишнього середовища у наслідку антропогенної дії. Виконано аналіз методологій що дозволяють кількісно виміряти ступінь впливу стану довкілля на здоров’я населення. З метою здійснення оцінки стану середовища у разі впливу негативних чинників ядерного паливного циклу України, запропоновано методологію оцінки ризику для здоров’я населення.

The overview of modern approaches to the procedure of the estimation of environmental objects condition at anthropogenic effect was made. Analysis of methodologies that allow to characterize quantitatively the extent of changes influence in the state of nature environment on men’s health was fulfilled. To realize estimation of the environmental state at the influence of the negative factors of Ukraine nuclear fuel cycle elements, the methodology of population health risk estimation was suggested
Keywords: атомная энергетика; радиационная безопасность; радиоактивные отходы; ядерный топливный цикл; антропогенное влияние; экологическая безопасность